Binary and Ternary Complexes of Cobalt(II) with Some Polydentate Ligands - Gupta, Lalit; Pandey, A.K.; Gupta, C.S. (Asian Journal of Chemistry, 2010)
Potentiometric investigations on binary and ternary complexes of Co2+ ion with multidentate ligands; 1,3-dihydroxy-4-(2'-pyridylazo) benzene (PAR, H2L); 1-(2'-arsonophenylazo)-2- hydroxynaphthalene-3,6-disulphonic acid (APANS, H5L); pyrogallol sulphonaphthalene (PGR, H4L) and the pair of ligands; PAR-ethylenediamine (en, A), PAR-1: 10-phenanthrolene (pn, A), APANS-en, APANS-pn, PGR-en, PGR-pn have been made in aqueous solution at 20oC and at an ionic strength of 0.1 M KNO3. The analysed experimental data indicate existence of CoHL+, CoHL(OH), CoL(OH)-, Co(HL)2, COHL2, CoL2-, CoHLA+ (with PAR, en and pn); CoLA (OH)- (with PAR and en)' CoH2L-, CoHL2-, CoL3-, CoH2LA-, CoHLA2- (with APANS, en and pn), CoLA3- (with APANS and en); CoL 2-, CoLA2- (with PGR, en and pn) species in steps. Equilibrium constants of these probable complex species have been evaluated and the structutes have been discussed.